ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT DELAY DAN KETEPATAN WAKTU PUBLIKASI LAPORAN KEUANGAN - Firman Dwi Laksono; Dul Muid (Diponegoro Journal of Accounting, 2014)
The purpose of this research is to analyze the factors that affect audit delay and timeliness of financial reports to the manufacturing consumer good sector companies listed on the Indonesia Stock Exchange The examined factors of this research are profitability, solvability, company size, the size of a public accounting firm and company age as the independent variables while  the  timeliness and audit delay as the dependent variables.The sample consists of 95 companies listed in the Indonesia Stock Exchange (IDX) and submitted financial reports to Bapepam consistently in the period 2010-2012. The data that was used in this research was secondary data and selected by using purposive sampling method. The analysis tool used is multiple regression analysis to measure audit delay, logistic regression to measure timeliness and  a the relationship between the timeliness of audit delay.As the results of the research, there are five factors have significant effect on audit delay. They are: 1) profitability, 2) solvability, 3) company size 4) size of the public accounting firm 5) age company. And profitability and solvability have significant effect on timeliness. As the results of logistic regression have significant effect between the timeliness of audit delay. The short time in auditing make the transaction due in exect time.